Preparation method of flame-retardant solid polymer electrolyte and application of flame-retardant solid polymer electrolyte in lithium battery

By reacting dichloropolyphosphazene with trifluoro and octafluoro nucleophilic reagents and combining them with polyvinylidene fluoride-hexafluoropropylene copolymer and inorganic filler, a flame-retardant solid polymer electrolyte is formed, which solves the problem of metal lithium batteries. The problems of low safety and ion conductivity achieve high conductivity and flame retardancy, improving the safety and circulation performance of lithium batteries.

CN119253053APending Publication Date: 2025-01-03BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411621036.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The combination of metal lithium and carbonate liquid electrolytes has safety problems in lithium batteries, such as limited electrochemical stability windows, electrolyte leakage and volatility, and may even lead to fire or explosion, and the polymer-based electrolyte has a low ionic conductivity. , limits its application.

Method used

Using a preparation method, by reacting dichloropolyphosphazene with trifluoro and octafluoro nucleophilic reagents in tetrahydrofuran, polymer FPZ is formed, and it is combined with polyvinylidene fluoride-hexafluoropropylene copolymer and inorganic filler lithium The combination of lanthanum zirconium tantalum oxygen oxides forms a flame-retardant solid polymer electrolyte, improving its ionic conductivity and flame retardancy.

Benefits of technology

A solid polymer electrolyte with high conductivity and flame retardancy is achieved, which improves the safety and circulation performance of lithium batteries, reduces the interface impedance, and effectively inhibits the growth of lithium dendrites, improves the oxidation resistance and resistance of the battery. Fueling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133444480000021
    Figure BDA0005133444480000021
  • Figure FDA0005133444430000011
    Figure FDA0005133444430000011
  • Figure HDA0005133444550000011
    Figure HDA0005133444550000011
Patent Text Reader

Abstract

The invention discloses a preparation method of a flame-retardant solid polymer electrolyte and application thereof in a lithium battery, and belongs to the field of lithium batteries. The specific preparation process of the flame-retardant solid polymer electrolyte comprises the following steps: dissolving trifluoro and octafluoro nucleophilic reagents and dichloropolyphosphazene in tetrahydrofuran, and carrying out nucleophilic substitution reaction to generate a linear trifluoro and octafluoro substituted phosphazene polymer FPZ; then, FPZ is added into a polyvinylidene fluoride-hexafluoropropylene mixed solution dissolved by ethylene glycol dimethyl ether, and the flame-retardant solid polymer electrolyte is obtained. The preparation raw materials of the flame-retardant solid polymer electrolyte also comprise an inorganic filler and a lithium salt. According to the invention, polyphosphazene is used as a flame retardant, the fluorinated structure of polyphosphazene enhances the compatibility with polyvinylidene fluoride-hexafluoropropylene, weakens the interaction with lithium ions, promotes the formation of an inorganic fluorinated SEI layer, and effectively inhibits the growth of lithium dendrites. The electrolyte provided by the invention has excellent flame retardant property and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing a flame-retardant solid polymer electrolyte and its application in lithium batteries. Background Art

[0002] With the rapid development of electric vehicles, energy storage, consumer electronics and other fields, the demand for high-safety and high-energy-density batteries has grown rapidly. Metal lithium has a high theoretical specific capacity (3860mAh g -1 ) and a lower negative potential (-3.04Vvs standard hydrogen electrode) have been considered as typical anode materials for next-generation high-energy density batteries. However, the combination of metallic lithium and carbonate liquid electrolytes faces a series of safety issues, such as limited electrochemical stability window, electrolyte leakage and volatilization, and even the risk of fire and explosion. In order to solve these problems, safe solid electrolytes have been proposed and developed to replace liquid electrolytes.

[0003] Solid electrolytes have good mechanical strength and a wide electrochemical stability window, and their thickness allows for high energy density. Among solid electrolytes, polymer-based electrolytes have attracted widespread attention due to their excellent processability, flexibility, and good interfacial compatibility, but the low ionic conductivity of polymer-based electrolytes has become a key issue to be addressed in their application.

[0004] The main chain of polyphosphazene is composed of P and N atoms arranged alternately with single and double bonds. Two flame retardant elements P and N exist at the same time. The two side groups connected to the phosphorus atom can be replaced by organic or inorganic functional groups. The unique structure and diversity of this inorganic-organic hybrid make polyphosphazene attract much attention. According to the synthesis route, phosphazene macromolecules are structurally divided into linear polyphosphazenes, cyclic polyphosphazenes and cyclolinear polyphosphazenes. At present, the research on polyphosphazenes mainly focuses on cyclotriphosphazenes, but their ionic conductivity is lower than that of linear polyphosphazenes. It has been confirmed that linear polyphosphazenes containing ether oxygen side groups have flame retardancy and better ionic conductivity, but solid electrolytes based on this type of polyphosphazene and their application in lithium batteries have not been reported. Therefore, it is particularly important to use linear polyphosphazenes to develop polymer electrolytes with high ionic conductivity and flame retardancy. Summary of the invention

[0005] In order to overcome the above problems in the prior art, one of the objectives of the present invention is to provide a solid polymer electrolyte having the advantages of good flame retardancy and high electrical conductivity.

[0006] A second object of the present invention is to provide a method for preparing the above-mentioned solid polymer electrolyte.

[0007] A third object of the present invention is to provide a lithium battery comprising the above-mentioned solid polymer electrolyte.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a method for preparing a flame retardant solid polymer electrolyte, the steps of the preparation method are as follows:

[0010] (1) dissolving dichloropolyphosphazene in tetrahydrofuran to obtain solution A;

[0011] (2) adding a trifluoro or octafluoro nucleophilic reagent to the solution A to obtain a solution B, heating the solution B, and mechanically stirring the solution B during the heating process to allow the dichloropolyphosphazene and the trifluoro or octafluoro nucleophilic reagent to undergo nucleophilic substitution to obtain a polymer named FPZ;

[0012] (3) adding the FPZ to a mixed solution of polyvinylidene fluoride-hexafluoropropylene copolymer dissolved in ethylene glycol dimethyl ether, adding an inorganic filler and a lithium salt, stirring evenly, pouring into a mold, and heating to evaporate the solvent to obtain a flame-retardant solid polymer electrolyte.

[0013] Preferably, in solution A of step (1), every 5 g of dichloropolyphosphazene corresponds to 100 ml of tetrahydrofuran.

[0014] Preferably, the specific steps of step (2) are: adding trifluoro and octafluoro nucleophiles dropwise to the solution A to obtain solution B, wherein the molar ratio of trifluoro and octafluoro nucleophiles is 2:1 to 1:2; heating solution B to 60-70°C, stirring for 72 hours, then stopping heating and cooling at room temperature for 6 hours to obtain solution C; filtering the solution C, and washing with deionized water and ethanol in turn to obtain a brown solid product; heating and drying the brown solid product to obtain FPZ.

[0015] The trifluoro nucleophile and the octafluoro nucleophile are sodium trifluoroethoxide and sodium octafluoropentanolate respectively.

[0016] According to an embodiment of the present invention, the structural formula of the polyphosphazene is shown in formula (1):

[0017]

[0018] Wherein, R and R' are the same or different, independent of each other, and are selected from at least one of CH2(CF2)3CF2H and CH2CF3. The molar ratio of CH2(CF2)3CF2H to CH2CF3 is 2:1 to 1:2.

[0019] According to an embodiment of the present invention, the inorganic filler is selected from lithium lanthanum zirconium tantalum oxide; the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), and lithium bis(fluorosulfonyl imide). More preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl imide).

[0020] Preferably, the lithium salt accounts for 40 wt% to 70 wt% of the solid polymer electrolyte, such as 50 wt%.

[0021] Preferably, the specific steps of step (3) are:

[0022] Dissolve polyvinylidene fluoride-hexafluoropropylene copolymer and polyphosphazene in ethylene glycol dimethyl ether to obtain a precursor solution; add inorganic filler and lithium salt to the precursor solution, stir evenly to obtain an electrolyte solution, cast the electrolyte solution into a polytetrafluoroethylene mold, and vacuum dry overnight at 70-75°C to obtain a flame-retardant solid polymer electrolyte PVDF-HFP-FPZ. Preferably, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene copolymer to the polyphosphazene FPZ is 1:(0.1-0.5); for example, 1:0.2. The mass percentage of the inorganic filler in the flame-retardant solid polymer electrolyte is 2.5-10wt%. For example, 5wt%.

[0023] According to the embodiment of the present invention, the mixing can be performed by a method known in the art, which is not specifically limited in the present invention.

[0024] In a second aspect, the present invention further provides a flame-retardant solid polymer electrolyte, which is prepared by the above-mentioned preparation method.

[0025] In a third aspect, the present invention further provides a method for preparing a lithium battery using a flame-retardant solid polymer electrolyte, the preparation method comprising the following steps:

[0026] (1) LiNi 0.8 Co 0.1 Mn 0.1 O2 powder: carbon black: polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a ratio of 8:1:1, ground evenly, and then coated on aluminum foil with a scraper, and dried to obtain NCM811 positive electrode sheet;

[0027] (2) A lithium battery was prepared using a metal lithium sheet as the negative electrode, an NCM811 electrode as the positive electrode, and PVDF-HFP-FPZ as a flame-retardant solid polymer electrolyte.

[0028] Preferably, the PVDF-HFP-FPZ membrane is prepared by the above preparation method.

[0029] In a fourth aspect, the present invention further provides a lithium battery with a flame-retardant solid polymer electrolyte, characterized in that the lithium battery is prepared by the above-mentioned lithium battery preparation method.

[0030] Beneficial Effects

[0031] Polyvinylidene fluoride-hexafluoropropylene copolymer and polyphosphazene can be blended to form a uniform, dense and flat polymer film, which provides an ion conductive channel, effectively improves the interface contact between the electrolyte and the lithium negative electrode, and reduces the interface impedance. The addition of inorganic filler lithium lanthanum zirconium tantalum oxide reduces the crystallinity, provides additional lithium ion transmission channels, and has a restraining effect on the growth of lithium dendrites. The polyfluorinated structure of polyvinylidene fluoride-hexafluoropropylene copolymer and polyphosphazene weakens the interaction with lithium ions, promotes the formation of inorganic fluorinated SEI, effectively inhibits the growth of lithium dendrites, and improves the cycle performance. Polyphosphazene compounds contain three flame retardant elements, fluorine, and nitrogen, which synergistically play a flame retardant effect, and the fluorine element is conducive to the formation of a fluoride-based SEI layer; it can also be adapted to the high-voltage positive electrode to improve oxidation resistance. Under the joint action of additives, the prepared solid polymer electrolyte not only has excellent flame retardancy, but also has a good high-voltage cycle retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a plane scanning electron microscope image of the blend of polyvinylidene fluoride-hexafluoropropylene copolymer and polyphosphazene in Example 1.

[0033] Figure 2 This is a flame retardant performance diagram of the solid polymer electrolyte of Example 1 and Comparative Example 1.

[0034] Figure 3 The performance diagram of NCM811 battery made of solid polymer electrolyte of Example 1 and Comparative Examples 1 and 2. Specific implementation methods

[0036] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0037] Example 1

[0038] (1) Preparation of FPZ polymer:

[0039] 5 g of dichloropolyphosphazene was dissolved in 100 ml of tetrahydrofuran to obtain solution A. Trifluoro and octafluoro nucleophiles (molar ratio 1:2) were added dropwise to the solution A to obtain solution B; the solution B was heated to 60-70°C, stirred for 72 hours, and then the heating was stopped and cooled at room temperature for 6 hours to obtain solution C; the solution C was filtered, and then washed with deionized water and ethanol in turn to obtain a brown solid product; the brown solid product was heated and dried to obtain FPZ.

[0040] (2) Preparation of solid polymer electrolyte:

[0041] In a glove box filled with argon (water content less than 1ppm, oxygen content less than 1ppm), polyvinylidene fluoride-hexafluoropropylene copolymer, polyphosphazene FPZ, and inorganic filler were dissolved in ethylene glycol dimethyl ether solution, stirred to dissolve, and then lithium bis(trifluoromethanesulfonyl imide) was added and stirred for 6 hours to obtain an electrolyte solution. In the electrolyte solution, the mass ratio of polyvinylidene fluoride-hexafluoropropylene copolymer to polyphosphazene was 1:0.3, the mass ratio of lithium bis(trifluoromethanesulfonyl imide to the total polymer was 1.5:1, and the mass ratio of inorganic filler lithium lanthanum zirconium tantalum oxide to the total polymer was 0.1:1. The electrolyte solution was poured into a polytetrafluoroethylene mold and vacuum dried overnight at 70°C to obtain a solid polymer electrolyte; it was prepared into a disc with a diameter of 16 mm.

[0042] (3) Preparation of positive electrode sheet:

[0043] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 powder (80wt%), carbon black (10wt%), and binder polyvinylidene fluoride (10wt%) were dissolved in N-methylpyrrolidone and stirred for 8h; the mixed positive electrode slurry was scraped on aluminum foil to prepare the positive electrode sheet. The positive electrode sheet was placed in a vacuum oven at 100℃ and dried for 12h, and cut to obtain NCM811 electrode sheet.

[0044] Preparation of lithium battery:

[0045] Move the dried positive electrode sheet into a glove box filled with argon atmosphere (moisture content less than 1 ppm, oxygen content less than 1 ppm), and then place the positive electrode sheet, solid polymer electrolyte, negative electrode lithium sheet, gasket, and shrapnel in order to assemble a button battery.

[0046] Comparative Example 1

[0047] This example provides a solid polymer electrolyte, which is basically the same as Example 1, except that polyphosphazene and inorganic filler lithium lanthanum zirconium tantalum oxide are omitted.

[0048] Comparative Example 2

[0049] This example provides a solid polymer electrolyte, which is basically the same as Example 1, except that polyphosphazene is omitted.

[0050] Performance Testing

[0051] 1. Flame retardant properties

[0052] The solid polymer electrolytes obtained in Example 1 and Comparative Example 1 were subjected to ignition experiments to test their flame retardancy. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that after the solid polymer electrolyte of Example 1 is ignited by flame, when the lighter is extinguished, it can be extinguished by itself when away from the flame. After being ignited again, when the fire source is removed, the solid polymer electrolyte membrane no longer burns, indicating that it has good flame retardancy. The solid polymer electrolyte prepared in Comparative Example 1 immediately burns violently after encountering flame until it is burned out, indicating that its flame retardancy is very poor, which is a common problem of conventional polymer electrolytes.

[0053] 2. Cycle performance

[0054] The solid polymer electrolytes obtained in Example 1 and Comparative Examples 1 and 2 were assembled into NCM811 batteries, and constant current charge and discharge experiments were carried out at a voltage of 3.0 to 4.2 V. The cycle results are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the NCM811 battery assembled by the solid polymer electrolyte of Example 1 has a high cycle life and high stability. The initial specific capacity can reach 208.9 mAh / g at 0.4C, and the capacity retention rate can still reach 80.04% after 150 cycles, and the coulombic efficiency remains at 99%. The NCM811 battery assembled by the solid polymer electrolyte of Comparative Example 1 has an initial specific capacity of 190.4 mAh / g at 0.4C, and a capacity retention rate of 52.2% after 150 cycles. The NCM811 battery assembled by the solid polymer electrolyte of Comparative Example 2 has an initial specific capacity of 181.9 mAh / g at 0.4C, and a capacity retention rate of 66.7% after 150 cycles. From the above comparison, it can be seen that the solid polymer electrolyte material prepared by the present invention has good cycle stability.

[0055] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a flame retardant solid polymer electrolyte, characterized in that: The steps of the preparation method are as follows: (1) dissolving dichloropolyphosphazene in tetrahydrofuran to obtain solution A; (2) adding a trifluoro or octafluoro nucleophilic reagent to the solution A to obtain a solution B, heating the solution B, and mechanically stirring the solution B during the heating process to allow the dichloropolyphosphazene and the trifluoro or octafluoro nucleophilic reagent to undergo nucleophilic substitution to obtain a polymer named FPZ; (3) adding the FPZ to a mixed solution of polyvinylidene fluoride-hexafluoropropylene copolymer dissolved in ethylene glycol dimethyl ether, adding inorganic fillers and lithium salts, stirring evenly, pouring into a mold, and heating to evaporate the solvent to obtain a flame-retardant solid polymer electrolyte PVDF-HFP-FPZ.

2. The method for preparing a flame-retardant solid polymer electrolyte according to claim 1, characterized in that: In solution A of step (1): every 5 g of dichloropolyphosphazene corresponds to 100 ml of tetrahydrofuran.

3. The method for preparing a flame-retardant solid polymer electrolyte according to claim 1, characterized in that: The specific steps of step (2) are: adding trifluoro and octafluoro nucleophiles dropwise to the solution A to obtain solution B, wherein the molar ratio of trifluoro and octafluoro nucleophiles is 2:1 to 1:2; heating solution B to 60-70°C, stirring for 72 hours, then stopping heating and cooling at room temperature for 6 hours to obtain solution C; filtering the solution C, and washing with deionized water and ethanol in turn to obtain a brown solid product; heating and drying the brown solid product to obtain FPZ; The trifluoro nucleophile and the octafluoro nucleophile are sodium trifluoroethoxide and sodium octafluoropentanolate respectively.

4. The method for preparing a flame-retardant solid polymer electrolyte according to claim 1, characterized in that: The structural formula of the FPZ is shown in formula (1): Wherein, R and R' are the same or different, independent of each other, and are selected from at least one of CH2(CF2)3CF2H and CH2CF3. The molar ratio of CH2(CF2)3CF2H to CH2CF3 is 2:1 to 1:

2.

5. The method for preparing a flame-retardant solid polymer electrolyte according to claim 1, characterized in that: The inorganic filler is selected from lithium lanthanum zirconium tantalum oxide; the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), and lithium bis(fluorosulfonyl imide). More preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl imide).

6. The method for preparing a flame-retardant solid polymer electrolyte according to claim 1, characterized in that: The mass percentage of the lithium salt in the solid polymer electrolyte is 40wt% to 70wt%, such as 50wt%; the mass ratio of the polyvinylidene fluoride-hexafluoropropylene copolymer to the polyphosphazene FPZ is 1:(0.1-0.5), for example, 1:0.2; the mass percentage of the inorganic filler in the flame-retardant solid polymer electrolyte is 2.5-10wt%, for example, 5wt%.

7. The method for preparing a flame-retardant solid polymer electrolyte according to claim 1, characterized in that: The specific steps of step (3) are: Dissolving polyvinylidene fluoride-hexafluoropropylene copolymer and polyphosphazene in ethylene glycol dimethyl ether to obtain a precursor solution; adding inorganic filler and lithium salt to the precursor solution, stirring evenly to obtain an electrolyte solution, pouring the electrolyte solution into a polytetrafluoroethylene mold, and vacuum drying overnight at 70-75°C to obtain a flame-retardant solid polymer electrolyte PVDF-HFP-FPZ.

8. A flame retardant solid polymer electrolyte prepared according to the method of any one of claims 1 to 7.

9. A lithium battery, characterized in that: The flame-retardant solid polymer electrolyte prepared by the method described in any one of claims 1 to 7 is used as the electrolyte.

10. A method for preparing a lithium battery using a flame retardant solid polymer electrolyte, the method comprising the following steps: (1) LiNi 0.8 Co 0.1 Mn 0.1 O2 powder: carbon black: polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a ratio of 8:1:1, ground evenly, and then coated on aluminum foil with a scraper, and dried to obtain NCM811 positive electrode sheet; (2) A lithium battery was prepared using a metal lithium sheet as the negative electrode, an NCM811 electrode as the positive electrode, and PVDF-HFP-FPZ as a flame-retardant solid polymer electrolyte.

Citation Information

Cited By

  • In-situ cross-linked flame-retardant polymer electrolyte and precursor solution and battery thereof

    CN121149395A